2019
DOI: 10.1093/mnras/stz2400
|View full text |Cite
|
Sign up to set email alerts
|

The VMC survey – XXXIV. Morphology of stellar populations in the Magellanic Clouds

Abstract: The Magellanic Clouds are nearby dwarf irregular galaxies whose morphologies show different properties when traced by different stellar populations, making them an important laboratory for studying galaxy morphologies. We study the morphology of the Magellanic Clouds using data from the VISTA survey of the Magellanic Clouds system (VMC). We used about 10 and 2.5 million sources across an area of ∼ 105 deg 2 and ∼ 42 deg 2 towards the Large and Small Magellanic Cloud (LMC and SMC), respectively. We estimated me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 89 publications
(160 reference statements)
5
19
0
1
Order By: Relevance
“…2 shows how we select the shape and size of the trapezoid. The shape is similar to that of region 'K' adopted by El Youssoufi et al (2019) to select the RGB population from VMC (Ks, J − Ks) CMDs to estimate morphological maps. We start by creating a density diagram by combining CMDs of subregions from different locations within the LMC: central region -tiles LMC 7 4 and 7 5; outer regions in all four directions -tiles LMC 2 5, 5 2, 6 9 and 9 3.…”
Section: Estimation Of the Rgb Slopesmentioning
confidence: 83%
See 1 more Smart Citation
“…2 shows how we select the shape and size of the trapezoid. The shape is similar to that of region 'K' adopted by El Youssoufi et al (2019) to select the RGB population from VMC (Ks, J − Ks) CMDs to estimate morphological maps. We start by creating a density diagram by combining CMDs of subregions from different locations within the LMC: central region -tiles LMC 7 4 and 7 5; outer regions in all four directions -tiles LMC 2 5, 5 2, 6 9 and 9 3.…”
Section: Estimation Of the Rgb Slopesmentioning
confidence: 83%
“…The SMC exhibits dynamically distorted features in its stellar populations because of interactions with the LMC (e.g. Nidever et al 2013;Subramanian et al 2017;El Youssoufi et al 2019;Niederhofer et al 2021;Gaia Collaboration et al 2021). Several distinct (sub)structures have been discovered in the LMC's outskirts (e.g.…”
mentioning
confidence: 99%
“…Centrally, the SMC displays a less prominent bar as well as an eastern wing structure first observed by Shapley (1940), departing from the northern end of the bar toward the LMC. Recent mapping of the SMC by El Youssoufi et al (2019) has shown the morphology of the younger stellar populations to be highly irregular and largely limited to the SMC bar and eastern wing, tracing the perturbed gaseous reservoir of the SMC (Stanimirović et al 2004), with recent star formation expected to have occurred in these regions (see, e.g., Irwin et al 1990;El Youssoufi et al 2019). The older stellar populations, on the other hand, display a much more homogeneous spatial distribution (see, e.g., Zaritsky et al 2000;Haschke et al 2012;Jacyszyn-Dobrzeniecka et al 2017) and indeed are offset from the younger populations, as observed by Mackey et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Neutral hydrogen gas within the SMC's main body has a prominent triangularly shaped distribution with an eastern extension, the SMC Wing, located towards the Magellanic Bridge. Young stars ( 300 Myr old) mainly follow the H I gas structure, while the old stellar population ( 5 Gyr old) is distributed in a more regular spheroid (Rubele et al 2015(Rubele et al , 2018El Youssoufi et al 2019b). Additionally, pulsating variable stars (young Cepheids and old RR Lyrae stars) trace an elongated structure of the SMC that extends more than 20 kpc along the line of sight (Jacyszyn-Dobrzeniecka et al 2016Ripepi et al 2017).…”
mentioning
confidence: 99%